URBAN COMMUNITY STRATEGIES IN FACING GLOBALIZATION CAUSES OF SOCIAL CHANGE - Yasin, Ahmad; Andari, Amalia; Nasution , Mukherzi (Academic Solution Publisher, 2024)
This journal discusses research on urban community strategies in facing social changes caused by globalization. Such as how to survive social and cultural changes as well as changes in people's lifestyles which may have an impact on changes in local values and characteristics. This research uses qualitative research methods with open interviews. The results of this research in the form of adaptation and adjustment to social change are strategies commonly used by urban communities to face globalization which causes social change, but accompanied by an agreement to protest changes that occur if they are not in accordance with local cultural values . Urban communities must choose what is good for their life in the city with the hope that their life is more decent compared to their life in their home region.